Persepsi Guru Penjas Terhadap Pembelajaran Daring di Tengah Pandemi Covid-19 Pada SMA Negeri Se-Kabupaten Jepara - Muhammad Izzama Indra Indra; Pandu Kresnapati; Fajar Ari Widiyatmoko (YLPK Mahardhika, 2020)
The purpose of this research is to see the perceptions of physical education teachers towards courageous learning in the midst of the Covid-19 pandemic at Public High Schools in Jepara Regency. There are also benefits, namely as an evaluation material for the knowledge of Physical Education teachers in SMA Negeri Jepara Regency. This research is a quantitative study using descriptive methods (Descriptive Research). The data of this study were sourced from the results of a survey on filling out a questionnaire by 28 Physical Education teachers in SMA Negeri Jepara Regency, in this case the teacher became a research. The data collected individually is descriptive based so that it does not seek explanations, hypotheses, make predictions, or learn implications. The results of this study indicate that the perceptions of Physical Education teachers towards courageous learning in the midst of the Covid-19 pandemic at Public High Schools throughout Jepara Regency are in the